PEMAHAMAN GURU PENDIDIKAN AGAMA KATOLIK TENTANG TUGAS MISIONER GEREJA DAN PELAKSANAANNYA DI SLTA KATOLIK KOTA MADIUN - Aloysius Iryanto; Don Bosco Karnan Ardijanto (Bahasa Indonesia, 2019)
The Sacrament of Baptism and of Confirmation urge the faithful to participate in the mission of the Church. One of various realizations of the Church’s mission is running the Catholic Schools. In other words, all members of a Catholic school: teachers, employees, students, foundations or parents, are called and sent to be involved in the mission of the Church. One of the fruits of carrying out Church missionary duties in Catholic schools is baptism. In 2012-2016 the number of baptisms in the Catholic High Schools in the city of Madiun was 15 people. Starting from the above, several questions can be asked as the starting point of this research: 1) What is the Church’s mission? 2) What is the Church’s mission according to the Catholoc religious educators? 3) How do the Catholic religious educators implement the Church’s mission in the Catholic Senior High Schools in Madiun city? This study aims: describing the understanding of the Church’s mission, to analyze the understanding of Religious Educators on the Church’s mission and to analyze how the religious educators to realize the Church’s mission in the Catholic Senior High Schools in the Madiun city. To achieve these objectives, researcher used qualitative research methods with interview techniques. The respondents of this study were religious educators in four Catholic Senior High Schools in Madiun. The results of the study show that: 1) The Religious Educators know the understanding of the Church’s mission. 2) All faithful are responsible to participate in the Church’s mission. 3) The Religious Educators had to be responsible and to involve in the Church’s mission in Catholic Senior High Schools. 4) The Religious Educators had already done and implemented the Church’s mission in their schools. In fact, there were some difficulties come from extern or intern of the schools.